Hereditary Spastic Paraplegia Is a Common Phenotypic Finding in ARG1 Deficiency, P5CS Deficiency and HHH Syndrome: Three Inborn Errors of Metabolism Caused by Alteration of an Interconnected Pathway of Glutamate and Urea Cycle Metabolism - Panza, Emanuele; Martinelli, Diego; Magini, Pamela; Dionisi Vici, Carlo; Seri, Marco (Frontiers in Neurology, 2019)
Hereditary Spastic Paraplegias (HSP) are a clinically and genetically heterogeneous group of neurodegenerative disorders characterized by a progressive rigidity and weakness of the lower limbs, caused by pyramidal tract lesions. Today eighty different forms of HSP have been mapped, sixty-four genes have been cloned, and new forms are constantly being described. HSPs represent an intensively studied field, and the functional understanding of the biochemical and molecular pathogenetic pathways are starting to be elucidated. Recently dominant and recessive mutations in the ALDH18A1 gene, resulting in the deficiency of the encoded enzyme (delta-1-pyrroline-5-carbossilate synthetase, P5CS), have been pathogenetically linked to HSP. P5CS is a critical enzyme in the conversion of glutamate to pyrroline-5-carboxylate, an intermediate that enters in the proline biosynthesis and that is connected with the urea cycle. Interestingly, two urea cycle disorders Argininemia and Hyperornithinemia-Hyperammonemia-Homocitrullinuria syndrome, are clinically characterized by highly penetrant spastic paraplegia. These three disease represent a peculiar group of HSPs caused by Inborn Errors of Metabolism. Here we comment on these forms, the common features among them and on a possible shared pathogenetic mechanism causing the HSP phenotype.